Tensile, impact and fiber length properties of injection-molded short and long glass fiber-reinforced polyamide 6,6 composites - Hassan, A.; Yahya, R.; Yahaya, A.H.; Tahir, A.R.M.; Hornsby, P.R. (2004)
Injection molding of fiber-reinforced polymer composites is associated with the problem of fiber breakage. If the fiber length retained in the finish product is too short, it will limit the expected improvement in the property. Extrusion and pultrusion are two methods normally employed for the melt compounding of polymer composite feedstock for the injection molding and produced short- and long-fiber composites (SFCs and LFCs), respectively. In this work, short-and long-glass fiber-reinforced polyamide 6,6 composites were injection molded at different fiber loading and tested for the tensile properties, impact properties and fiber length characteristics. It was found that both tensile strength and tensile modulus of LFCs improved compared to the SFCs counterpart despite reduction in fracture strain, while pultrusion compounded composites also showed superior fiber characteristics, in terms of fiber length distribution, L n, L w, etc. compared to the extrusion compounded composites counterpart. Fiber length characteristics were also in agreement with the improvement in tensile strength and tensile modulus of LFCs over the SFCs. Impact properties of LFCs also show some improvement compared to the SFCs counterpart with equivalent composition, despite longer fiber retained in composites.